Analisis Ayat-Ayat Al-Qur’an Sebagai Landasan Dakwah - Ningsih, Widia; Satriah , Lilis (Bahasa Indonesia, 2024)
To properly understand da'wah, it must be through understanding the Qur'an as the main source of da'wah. However, the Qur'an can only be properly understood through interpretation. The purpose of this research is to analyze the verses of the Qur'an that are the basis of da'wah. This analysis is expected to provide a deeper understanding of the purpose and method of da'wah in accordance with the foundation of the Qur'an. The urgency of this research is made because effective da'wah can bring great benefits to individuals, communities, and nations. By understanding the foundation of da'wah from the Qur'an, it is hoped that dai and missionaries can carry out their duties better and optimally. This study uses a qualitative research method with a thematic interpretation approach. Based on the results of analysis and literature studies from various references, the results of this study are by understanding the foundation, purpose and method of da'wah according to the foundation in the Qur'an. His words are in Q.S Q.S Al-Baqarah: 214 and Q.S Al-Imron: 159 about the purpose of da'wah that this verse expressly explains that to obtain heaven from Allah, it is not enough just by faith. Muslims will be given various kinds of trials as befell the previous ummah as a test for them. Furthermore, in the Qur'an, Surah An-Nahl · Verse 125 conveys that Allah swt gives guidelines to His Messenger on how to invite people (da'wah) to the way of Allah